A γ-Fe2O3-modified nanoflower-MnO2/attapulgite catalyst for low temperature SCR of NOx with NH3. (18th January 2019) - Xie, Aijuan; Tao, Yiyang; Jin, Xiang; Gu, Pengfei; Huang, Xiaoyan; Zhou, Xingmeng; Luo, Shiping; Yao, Chao; Li, Xiazhang
Abstract : A novel mesoporous γ-Fe2 O3 -modified nanoflower-MnO2 /attapulgite catalyst has been fabricated through a facile hydrothermal method and used for low temperature SCR of NO x with NH3 . Abstract : A mesoporous γ-Fe2 O3 -modified nanoflower-MnO2 /attapulgite (γ-Fe2 O3 /nf-MnO2 –ATP) catalyst was fabricated through a facile hydrothermal method. The results of TEM and XRD indicated that γ-Fe2 O3 /nf-MnO2 –ATP presented a beautiful nanoflower shape and good dispersion. The BET results showed that the specific surface area and pore volume of γ-Fe2 O3 /nf-MnO2 –ATP significantly increased after surface modification with γ-Fe2 O3 . Also, the XPS and NH3 -TPD results illustrated that the γ-Fe2 O3 coating could enhance the amounts of surface chemisorbed oxygen and acidic sites. SO2 and H2 O tolerance tests and stability tests demonstrated that γ-Fe2 O3 /nf-MnO2 –ATP can effectively inhibit SO2 and H2 O poisoning and improve the stability of the catalyst. The superior SCR performance can be attributed to the abundant acid sites, the strong adsorption of NO x, and the formation of more oxygen vacancies as well as metal–metal interactions. Therefore, γ-Fe2 O3 /nf-MnO2 –ATP was proved to be an excellent catalyst for NH3 -SCR and may be of interest in other environmental catalysis applications.